Implementation of Cognitive Behavioral Therapy Counseling Program in Overcoming Online Game Addiction Among Grade X Students at MAN 1 Musi Banyuasin - Jumiati, Jumiati; Berlian, Zainal; Afriantoni, Afriantoni (Journal of Educational Sciences, 2025)
Online gaming addiction has a negative impact on students' social, cognitive, and behavioral aspects. This study aims to determine the implementation of Cognitive Behavior Therapy (CBT) counseling in treating online gaming addiction among 10th grade students at MAN 1 Musi Banyuasin. The method used was qualitative with techniques of interviews, observation, and documentation of the guidance counselor, principal, students, and homeroom teachers. The CBT counseling program was carried out in five stages: identification, diagnosis, prognosis, therapy, and evaluation. Each stage was conducted in five weekly sessions for one to three months. The strategies applied included cognitive restructuring, reinforcement of positive behavior, and increased social awareness. The results of the study showed that CBT was effective in reducing online game addiction. The changes experienced by students included a decrease in playing time, a reduction in obsessive thoughts about games, the disappearance of anxiety when prohibited from playing, increased awareness of the importance of prioritizing activities, and the ability to recognize and avoid negative behavior. CBT counseling has proven to be an effective and systematic approach to treating online gaming addiction in educational settings. Madrasah support, parental involvement, and student commitment are important factors in the success of this program.